2009
DOI: 10.1016/j.icarus.2008.11.023
|View full text |Cite
|
Sign up to set email alerts
|

Ice lines, planetesimal composition and solid surface density in the solar nebula

Abstract: To date, there is no core accretion simulation that can successfully account for the formation of Uranus or Neptune within the observed 2-3 Myr lifetimes of protoplanetary disks. Since solid accretion rate is directly proportional to the available planetesimal surface density, one way to speed up planet formation is to take a full accounting of all the planetesimal-forming solids present in the solar arXiv:0806.3788v2 [astro-ph] 4 Dec 2008 -2nebula. By combining a viscously evolving protostellar disk with a ki… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
112
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 136 publications
(116 citation statements)
references
References 84 publications
4
112
0
Order By: Relevance
“…The snow line has been located within or nearby the asteroid belt (Lunine, 2006;Cyr et al, 1998), and, following the recent nebular kinetics models results, it may have migrated as the nebula evolved, sweeping across the entire asteroid belt (Dodson-Robinson et al, 2009). According to the latest dynamical models, it has also been suggested that part of the main belt primitive asteroids were formed either between the giant planets or in the Trans-neptunian region (Walsh et al, 2011), and then injected into the inner Solar System.…”
mentioning
confidence: 99%
“…The snow line has been located within or nearby the asteroid belt (Lunine, 2006;Cyr et al, 1998), and, following the recent nebular kinetics models results, it may have migrated as the nebula evolved, sweeping across the entire asteroid belt (Dodson-Robinson et al, 2009). According to the latest dynamical models, it has also been suggested that part of the main belt primitive asteroids were formed either between the giant planets or in the Trans-neptunian region (Walsh et al, 2011), and then injected into the inner Solar System.…”
mentioning
confidence: 99%
“…This result is simplistic as it assumes a bare grain sitting alone at 1 AU with approximate grain properties. However, more detailed radiation transfer calculations confirm the general picture [70,71,72,73]. This well known result suggests that the solar nebular disk, and extra-solar protoplanetary disks, should have what is called a "snow-line".…”
Section: Chon In the Context Of Planetary Birthmentioning
confidence: 62%
“…We set up an experiment to test our hypothesis that the same model protostellar disk that produced Saturn, containing 8.6 g cm −2 of planetesimals at 9.5 AU (Dodson- Robinson et al 2008Robinson et al , 2009, with surface density doubled to match the heavy element content of HD 149026, could account for HD 149026b's large core. In a successful outcome, the planet would reach its current mass within a typical disk lifetime of 2-3 Myr (Haisch et al 2001) and contain the observed proportion of solid core and atmospheric gas.…”
Section: Simulation Results and Discussionmentioning
confidence: 99%
“…At 1.3 solar masses, HD 149026b is essentially a Sun-like star, so we begin by assuming its protostellar disk had the same total mass (gas+solid) as the solar nebula. We reconstruct the solid surface density profile Σ(R) of the HD 149026b disk by scaling the Σ(R) curves predicted for the solar nebula (Dodson- Robinson et al 2009) upward by a factor of 2. Figure 1 shows time shapshots of Σ(R) during the planetesimal-building epoch of the HD 149026 disk.…”
Section: Initial Conditions For Planet Formationmentioning
confidence: 99%